Path of Silibinin from diet to medicine: A dietary polyphenolic flavonoid having potential anti-cancer therapeutic significance. (August 2021) - Tuli, Hardeep Singh; Mittal, Sonam; Aggarwal, Diwakar; Parashar, Gaurav; Parashar, Nidarshana Chaturvedi; Upadhyay, Sushil Kumar; Barwal, Tushar Singh; Jain, Aklank; Kaur, Ginpreet; Savla, Raj; Sak, Katrin; Kumar, Manoj; et al.
Abstract: In the last few decades, targeting cancer by the use of dietary phytochemicals has gained enormous attention. The plausible reason and believe or mind set behind this fact is attributed to either lesser or no side effects of natural compounds as compared to the modern chemotherapeutics, or due to their conventional use as dietary components by mankind for thousands of years. Silibinin is a naturally derived polyphenol (a flavonolignans), possess following biochemical features; molecular formula C25 H22 O10, Molar mass: 482.44 g/mol, Boiling point 793 °C, with strikingly high antioxidant and anti-tumorigenic properties. The anti-cancer properties of Silibinin are determined by a variety of cellular pathways which include induction of apoptosis, cell cycle arrest, inhibition of angiogenesis and metastasis. In addition, Silibinin controls modulation of the expression of aberrant miRNAs, inflammatory response, and synergism with existing anti-cancer drugs. Therefore, modulation of a vast array of cellular responses and homeostatic aspects makes Silibinin an attractive chemotherapeutic agent. However, like other polyphenols, the major hurdle to declare Silibinin a translational chemotherapeutic agent, is its lesser bioavailability. After summarizing the chemistry and metabolic aspects of Silibinin, this extensive review focuses on functional aspects governed by Silibinin in chemoprevention with an ultimate goal of summarizing the evidence supporting the chemopreventive potential of Silibinin and clinical trials that are currently ongoing, at a single platform.